SUSTAINABLE WILD COLLECTION: REQUIREMENTS FOR RESOURCE MANAGEMENT AND RESOURCE USE FOR NATURAL INGREDIENTS - Duerbeck, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Following-up on the implementation of the WHO Guidelines on Good Agricultural and Collection Practices (GACP) for Medicinal Plants (WHO 2003), organic certification of wild collection and the International Standard for Sustainable Collection of Medicinal and Aromatic Plants (ISSC-MAP) focus on ecological aspects of GACP and the need for thorough but cost-effective resource assessments and the determination of sustainable yields. Social Accountability and Fair Trade have become important indicators to select business partners in a global market place. There are a number of approaches and label schemes available; however, they are not applicable for most wild collection products in a global market. A newly developed FairWild Standard (www.fairwild.org), which was set up by SIPPO and FairWild Foundation, allows collectors, workers and companies in the wild collection trade to jointly work on truly sustainable production and to receive a fair price for their goods. A small premium price shall be paid for certified products, which allows for social community projects in the collection areas. For all these processes, Standard Operating Procedures (SOPs) are developed. These SOPs for botanical identification, identification of collection areas and access rights, and resource assessments are complemented with SOPs in the form of a Collectors’ Manual and Plant Monographs, which are to provide guidance during the collection, followed by an SOP for Post Harvest dealing with the procedures in the collection stations. The final goal of the process documentation is to prepare for proper documentation for GMP, GACP and the above mentioned standards.